Faktor – Faktor yang Berhubungan dengan Kepatuhan Pengunjung Terhadap Protokol Kesehatan COVID-19 di BTKLPP Kelas I Palembang - Firdaus; Arie Wahyudi; Hamyiarti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The implementation of the health protocol will not run smoothly if the community does not support and does not participate, then the government needs appropriate efforts to increase community compliance in implementing the health protocol. This study aims to identify factors related to compliance with the COVID-19 health protocol. This research method uses a survey method that measures the independent and dependent variables, the analysis used is the chi square test. This research was conducted on 05-20 July 202. The instrument used was a questionnaire given to visitors with a total sample of 77 respondents with accidental sampling technique. The results of this study were found in the variable Age, most of the early adults were 65 (84.4%), education was mostly advanced education (49 (63.6%), Knowledge was mostly good 39 (50.6%), attitude was mostly good 53 (68.8%), mostly good motivation 45 (58.4%) and compliance mostly 50 (64.9%). with adherence to the COVID-19 health protocol, advice for BTKLPP Class I to always improve education in complying with health protocols and be firm with visitors who violate the COVID-19 health protocol to prevent the spread of COVID-19.